1983
DOI: 10.3382/ps.0622022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lactobacillus Inoculation and Antibiotic Feeding of Chickens on Availability of Dietary Biotin

Abstract: Oral inoculation with Lactobacillus acidophilus and dietary supplementation with antibiotics were compared in broiler chicks fed various levels of biotin to determine their effect on the biotin status of the chicks. Lactobacillus acidophilus inoculation of broiler chickens fed a diet marginally deficient in biotin (56 micrograms/kg) caused a significant decrease (P less than .01) in their liver biotin content from 1596 to 931 ng/g. The decrease biotin status was confirmed by significant increases (P less than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
1
2

Year Published

1986
1986
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 24 publications
2
2
1
2
Order By: Relevance
“…B 6 240 mg; Vit. B 12 2,000 mcg; Biotin 8 mg; Niacin 2,000 mg; Pantothenic Acid 1,200 mg; Folic Acid 80 mg; Choline 40,000 mg; I 200 mg; Se 60 mg; Fe 10,000 mg; Cu 2,400 mg; Zn 12,000 mg; Mn 14,000 mg; Antioxidant 10,000 mg. corroborate the findings of Buenrostro & Kratzer (1983) and Sugeta et al (2004), but are nevertheless opposite to those reported by Santoso et al (1995), Yeo & Kim (1997), Cavazzoni et al (1998) and Moreira et al (2001).…”
Section: Experimental Dietscontrasting
confidence: 42%
See 1 more Smart Citation
“…B 6 240 mg; Vit. B 12 2,000 mcg; Biotin 8 mg; Niacin 2,000 mg; Pantothenic Acid 1,200 mg; Folic Acid 80 mg; Choline 40,000 mg; I 200 mg; Se 60 mg; Fe 10,000 mg; Cu 2,400 mg; Zn 12,000 mg; Mn 14,000 mg; Antioxidant 10,000 mg. corroborate the findings of Buenrostro & Kratzer (1983) and Sugeta et al (2004), but are nevertheless opposite to those reported by Santoso et al (1995), Yeo & Kim (1997), Cavazzoni et al (1998) and Moreira et al (2001).…”
Section: Experimental Dietscontrasting
confidence: 42%
“…According to Buenrostro & Kratzer (1983), the decrease that was seen in performance when probiotics were given to birds might have resulted from a series of factors, among those, inadequate dosing of microorganisms, lack of sanitary challenge, as well as competition with the host for nutrients.…”
Section: Experimental Dietsmentioning
confidence: 99%
“…Markkanen (1960) observed no effect of neomycin on urinary biotin excretion. The rise in faecal biotin excretion associated with antibiotic treatment is in accordance with earlier findings of a higher liver biotin concentration in poultry following antibiotic supplementation (Buenrostro & Kratzer, 1983). The evidence presented may also be taken to estimate the supply of biotin by colonic bacteria.…”
Section: Discussionsupporting
confidence: 88%
“…Outro fator que leva a incidência da dermatite de contato por deficiência de biotina, em frangos de corte, é a inoculação de Lactobacillus acidophilus, pois estes micro-organismos competem pela biotina dietética (BUENROSTRO & KRATZER, 1983).…”
Section: Descrição E Causas De Pododermatiteunclassified